The impact of visceral fat and blood flow velocity in hypertensive subjects running head: The impact of visceral fat and blood flow velocity - A Rahman, Rasyada; Hamdon, Zulaika; Akutagawa, Masatake; Takahiro, Emoto; Kinouchi, Yohsuke; Azhim, Azran (iMedPub, 2016)
Objective: The aim of study is to assess health condition using data from blood flow velocity (BFV) measurement. We investigate the impact of different visceral fat (VF) level on BFV in normotensive and hypertensive subjects to predict health risk.